Study on The Starch Granules Morphology of Local Varieties of Dioscorea hispida and Dioscorea alata - Fauziah, Fauziah; Mas'udah, Shofiyatul; Hendrian, Hendrian (Journal of Tropical Life Science, 2016)
Starch is regarded as vital in the food industry, where granule size and shape determine its function and uses. One plant taxon that is widely known as a starch source is Dioscorea (Dioscoreaceae), whose starch and protein content make it a healthy food. As the initial step to identify which varieties possess potential as starch sources, we conducted study on starch granule morphology of some local varieties of D. hispida and D. alata. The aim of this study was to determine shape and size variation of starch granule of each variety of D. hispida and D. alata. The results showed that starch granule morphology does not only vary between species of D. hispida and D. alata, but also among varieties of those species. The shape of starch granules in D. hispida is dominantly polygonal (polyhedral). It showed similar results as those reported by other authors in their studies, except that â€“ in this study - we found there is also a triangular shape, which has never been reported before. Starch granule size of D. hispida is found to be â€œVery small â€“ Smallâ€ and only 1 variety of the species â€“ that is gadung jahe â€“ is classified as â€œSmallâ€ type. According to previous studies, varieties with small type starch granule are recommended as potential sources for non-food industrial raw materials. The shape of starch granules in D. alata is similar to those reported in other studies, which is dominantly triangular and polygonal; the size is classified as â€œMediumâ€ type, except for two varieties that are uwi ratu and uwi ulo (DC5), which are classified as â€œLargeâ€. According to previous studies, varieties with large type starch granule are recommended as potential sources for food. Thus, from this study 3 potential local varieties are identified, i.e. gadung jahe of D. hispida, and uwi ratu & uwi ulo of D. alata.